2021
DOI: 10.1111/odi.14103
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in human gingival fibroblasts from periodontitis versus healthy counterparts

Abstract: Reactive oxygen species (ROS) are major normal byproducts of aerobic metabolism, and their levels are highly increased under oxidative stress conditions (Xu et al., 2020). The increased levels of ROS usually suggest activated mitochondrial oxidative phosphorylation, led to the accumulation of inflammatory responses (Li & Qin, 2018).Many factors such as periodontal pathogenic bacteria and the host immune response contributing to chronic periodontitis (CP) are associated with oxidative stress (Chen et al., 2019)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Exceeding levels of ROS can trigger mPTP opening via mitochondrial ATP-sensitive potassium channels, and voltage-dependent anion channel-1 oligomerization, suggesting that ROS works as an important molecular leading to downstream mPTP opening and eventually disruption of cellular functions [ 47 , 48 ]. Of note, earlier, Bullon's work together with our recent work demonstrated that HGFs and gingival tissues from CP patients were observed impaired mitochondria and higher oxidative stress [ 8 , 12 , 49 ]. As a result of cellular ROS and mtROS outburst, mPTP opening can be activated.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Exceeding levels of ROS can trigger mPTP opening via mitochondrial ATP-sensitive potassium channels, and voltage-dependent anion channel-1 oligomerization, suggesting that ROS works as an important molecular leading to downstream mPTP opening and eventually disruption of cellular functions [ 47 , 48 ]. Of note, earlier, Bullon's work together with our recent work demonstrated that HGFs and gingival tissues from CP patients were observed impaired mitochondria and higher oxidative stress [ 8 , 12 , 49 ]. As a result of cellular ROS and mtROS outburst, mPTP opening can be activated.…”
Section: Discussionmentioning
confidence: 96%
“…Owing to the mtDNA accumulation in the plasma of CP mice, little is known about the mtDNA function and activity in HGFs during periodontitis. In the context of periodontitis, in vitro studies of periodontitis patients have confirmed alterations in mitochondrial structure, function, and hyperoxidative stress in HGFs and gingival tissues compared to normal individuals [ 8 , 12 ], which indicates that there may be a correlation between periodontitis progression and mitochondrial dysfunction in HGFs from different hosts. Interestingly, we confirmed that aberrant mtDNA release into cytosol and supernatants of HGFs from CP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a hallmark of multiple diseases, including periodontitis. Recent study indicates that human gingival fibroblasts from periodontitis exhibits enhanced ROS production [12]. ROS has been regarded as a "double-edged" sword in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis-induced oxidative stress can trigger proinflammatory mechanisms and importantly osteoclastogenesis, which then leads to the bone loss that is observed in patients with periodontitis [ 8 ]. It has been reported that oxidative stress can activate NF- κ B signaling pathway to promote the expression of proinflammatory factors [ 9 ]. Antioxidant therapy can reduce oxidative stress damage and alleviate alveolar bone loss in periodontitis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%